The AHS-R: A holistic thinking measure with expanded theoretical domains and improved score reliability - Ezgi Aytürk; Nilüfer Göktaş; Nagihan Özman; Emre Kayatepe; Rüya Su Şencan; S. Adil Sarıbay (PLoS ONE, 2026)
Analytic and holistic thinking represent distinct cognitive styles. The existing Analysis-Holism Scale (AHS) is the most widely used measure of holistic thinking but has faced psychometric challenges and its validation has been largely restricted to a limited cultural context. The purpose of this study was to develop a refined measurement instrument, the AHS-R (Analysis-Holism Revised Scale), that expands the theoretical representation of the holistic cognition domains by differentiating between the Midway (preference for compromise) and Contradiction (tolerance for contradiction) dimensions and offers improved psychometric properties for use in broader populations. Using Turkish samples, Study 1 ( N = 346) confirmed the feasibility of new items developed to more precisely and reliably represent Midway and Contradiction. Study 2 ( N = 631) applied item response theory (IRT) and hierarchical factor analytic models on the finalized scale with four dimensions (Causality, Midway, Contradiction, and Attention). The original Perception of Change subscale was removed due to its negative factor loading on the higher-order holistic thinking factor. IRT analysis showed that measurement properties were optimized by collapsing the original 7-point rating scale to a 4-point scale. A structural equation model confirmed the presence of a dominant general holistic thinking factor and provided preliminary evidence of construct validity, showing that the unique variance of all four dimensions was significantly and positively related to increased adherence to preventive health behaviors during COVID-19. The newly developed AHS-R is a robust instrument for measuring holistic thinking that addresses key limitations of the original AHS by expanding its theoretical domains, notably through the clear distinction between the Midway and Contradiction subscales, and enhancing reliability. These improvements allow for more precise measurement, facilitating interpretation of scores across different levels of analysis. Ultimately, AHS-R supports further cross-cultural research into the relationship between cognitive style and behavior, such as health engagement.